Implementasi Epistemologi Irfani dalam Membentuk Keluarga Sakinah, Mawadah, Warahmah - NurKhoiriyah, Siti; Achmad Khudori Soleh; Wulan Nur Diana (Mukaddimah: Jurnal Studi Islam, 2024)
This research discusses the implementation of Irfani epistemology in forming a sakinah mawadah warahmah family. The aim of this research is to find out if the Irfani epistemology is implemented in the family to form a sakinah mawadah warahmah family. This research method is library research with data analysis techniques. This research uses primary data sources and secondary data sources. Research results [1] Irfani's epistemology is a disclosure of knowledge obtained through illuminating the essence of God to His servants (kasyf) [2] The Sakinah Mawadah Warahmah family is a family built on the basis of a valid marriage, which is able to fulfill spiritual and material needs legally worthy and balanced, filled with affection between family members. [3] If the Irfani way of thinking is applied in the family, all problems in the household will be made easier and disappear because all problems no longer use human or worldly glasses but use higher glasses, namely divine glasses. So this creates a sakinah mawadah warrahmah family.